Case report of bilateral relapsing-remitting sciatic nerve palsy during two pregnancies. (December 2015) - Suntrup-Krueger, Sonja; Schilling, Matthias; Schwindt, Wolfram; Wiendl, Heinz; Meuth, Sven
Abstract Background Unlike puerperal peripheral nerve lesions, mononeuropathy during pregnancy is rarely encountered. We report a case of bilateral relapsing-remitting sciatic nerve palsy during two pregnancies. An extensive literature search in PubMed brought no similar cases. Case presentation A healthy young woman presented with initially unilateral sciatic nerve palsy, which manifested and worsened during the early phases of two successive pregnancies. Electrophysiology revealed axonal lesion of the sciatic nerve with predominant affection of the peroneal part. Extensive laboratory examination including cerebrospinal fluid examination was unremarkable. MR imaging was compatible with bilateral intraneural perineurioma. Recurrent occurrence during two pregnancies and an anamnestic relationship between intermediate worsening of the paresis and the menstrual cycle suggested hormone-dependency of the tumor. However, response to repeated intravenous immunoglobuline (IVIG) therapy during pregnancy and shortly after childbirth resulted in partial reversion of foot drop. This was also indicative of an immunoneuropathy. Nerve biopsy was not performed because of clinical improvement. The precise underlying neuropathological mechanism remained unclear. Conclusion To increase knowledge and awareness of this rare entity, potential etiologies of mononeuropathies during pregnancy are discussed in the context of this case report. In the rare occasion of peripheral nerve mononeuropathy during pregnancy, in which therapeutic opportunities are limited, IVIG therapy may be an option when the etiology cannot clearly be determined after thorough medical investigation.